2018
DOI: 10.1101/242446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM structure of an early precursor of large ribosomal subunit reveals a half assembled intermediate

Abstract: Assembly of eukaryotic ribosome is a complicated and dynamic process that involves a series of intermediates. How the highly intertwined structure of 60S large ribosomal subunits is established is unknown.Here, we report the structure of an early nucleolar pre-60S ribosome determined by cryo-electron microscopy at 3.7 Å resolution, revealing a half assembled subunit. Domains I, II and VI of 25S/5.8S rRNA tightly pack into a native-like substructure, but domains III, IV and V are not assembled. The structure co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…The role of this family of helicase proteins is to unwind RNA structures and/or RNA-protein complexes, thus they are highly involved in ribosome maturation. Mt-LAF1 shows similarity with Has1, previously described in yeast pre-60S maturation and with Mss116, involved in yeast mitoribosome maturation 13,14 (Extended Data Fig. 7).…”
Section: Intersubunit Sidementioning
confidence: 53%
“…The role of this family of helicase proteins is to unwind RNA structures and/or RNA-protein complexes, thus they are highly involved in ribosome maturation. Mt-LAF1 shows similarity with Has1, previously described in yeast pre-60S maturation and with Mss116, involved in yeast mitoribosome maturation 13,14 (Extended Data Fig. 7).…”
Section: Intersubunit Sidementioning
confidence: 53%
“…Further transcription does not lead to the addition of many additional factors, since domains III-V are flexible in the early stages of pre-60S maturation (Supplemental Fig. 2), as seen in the cryo-EM structure of nucleolar pre-60S particles (Kater et al 2017;Sanghai et al 2018;Zhou et al 2018). Completion of domain VI induces the incorporation of almost 20 ribosome assembly factors, the 5S rRNA and association of snR10.…”
Section: Resultsmentioning
confidence: 96%
“…Recent structures of nucleolar pre-60S particles have revealed some of the folding pathways that large subunit pre-rRNA follows (Kater et al 2017;Sanghai et al 2018;Zhou et al 2018) showing that domains I, II, and VI of the 25S rRNA, along with the 5.8S rRNA, fold first into a near-mature conformation. Domains III-V remain unfolded in the early stages of large subunit assembly.…”
Section: Introductionmentioning
confidence: 99%
“…No overall particle structure is available, although a recent high throughput pre-rRNA probing has provided important insights into the folding of the 35S and 27SA2 pre-rRNAs [ 7 ]. Moreover, very recently, structures of nucleolar pre-60S particles have been reported that seem to lack the Npa1p complex and probably correspond to particles closely downstream from the first pre-60S particle in the maturation pathway [ 11 13 ]. Of the approximately 30 AFs present in the first pre-60S particle [ 6 ], a third are required for its production and/or stability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that formation and clustering of the root helices, as well as folding of domain I that forms part of the solvent exposed surface of the large subunit, are key events that take place very early on during large subunit biogenesis and are prerequisites for all downstream maturation steps [ 10 ]. The recently published cryo-EM structures of yeast nucleolar pre-60S particles [ 11 13 ] support the idea that assembly of the large ribosomal subunit starts with the folding and stabilization of domain I followed by those of domains II and VI.…”
Section: Introductionmentioning
confidence: 88%